Characterization of the inhalable fraction (< 10 μm) of soil from highly urbanized and industrial environments: magnetic measurements, bioaccessibility, Pb isotopes and health risk assessment - Menegaki, Stavroula; Kelepertzis, Efstratios; Kypritidou, Zacharenia; Lampropoulou, Anastasia; Chrastný, Vladislav; Aidona, Elina; Bourliva, Anna; Komárek, Michael (Environmental geochemistry and health, 2024)
Soil in urban and industrial areas is one of the main sinks of pollutants. It is well known that there is a strong link between metal(loid)s bioaccessibility by inhalation pathway and human health. The critical size fraction is < 10 μm (inhalable fraction) since these particles can approach to the tracheobronchial region. Here, soil samples (< 10 μm) from a highly urbanized area and an industrialized city were characterized by combining magnetic measurements, bioaccessibility of metal(loids) and Pb isotope analyses. Thermomagnetic analysis indicated that the main magnetic mineral is impure magnetite. In vitro inhalation analysis showed that Cd, Mn, Pb and Zn were the elements with the highest bioaccessibility rates (%) for both settings. Anthropogenic sources that are responsible for Pb accumulation in < 10 μm fraction are traffic emissions for the highly urbanized environment, and Pb related to steel emissions and coal combustion in cement plant for the industrial setting. We did not establish differences in the Pb isotope composition between pseudo-total and bioaccessible Pb. The health risk assessment via the inhalation pathway showed limited non-carcinogenic risks for adults and children. The calculated risks based on pseudo-total and lung bioaccessible concentrations were identical for the two areas of contrasting anthropogenic pressures. Carcinogenic risks were under the threshold levels (CR < 10-4), with Ni being the dominant contributor to risk. This research contributes valuable insights into the lung bioaccessibility of metal(loids) in urban and industrial soils, incorporating advanced analytical techniques and health risk assessments for a comprehensive understanding.
Keywords: inhalační expozice; Source identification; Metals, Heavy; Humans; Urbanization; olovo; dítě; Inhalation Exposure; Respiratory bioaccessibility; Magnetite; Child; Environmental Monitoring; průmysl; látky znečišťující půdu; Soil Pollutants; dospělí; Isotopes; biologická dostupnost; Industry; půda; Lead; lidé; velikost částic; Biological Availability; Cities; Adult; monitorování životního prostředí; těžké kovy; urbanizace; izotopy; Risk Assessment; Soil; velkoměsta; Particle Size; Urban geochemistry; hodnocení rizik